2016
DOI: 10.14775/ksmpe.2016.15.5.086
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Fabrication of 3D Porous Scaffold Combined with Polymer Deposition System and a Salt Leaching Method

Abstract: In this study, we used a polymer deposition system, based on fused deposition modeling, to fabricate the 3D scaffold and then fabricated micro-pores on a 3D scaffold using a salt leaching method. Materials included polycaprolactone (PCL) and sodium chloride (NaCl). The 3D porous scaffolds were fabricated according to blending ratio such as PCL (70 wt%)/NaCl (30 wt%) and PCL (50 wt%)/NaCl (50 wt%). The 3D porous scaffolds were observed by scanning electron microscopy. The results showed that 3D porous scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In order to solve this problem, the use of a suitable temporary porogen has been reported many times in previous studies 18 . Shim et al 19 have reported that NaCl can be a good porogen in the PCL matrix due to its good solubility in water and nontoxic effect on living cells. In the other study, Guarino et al 20 showed that the yield stress of PCL scaffolds by the addition of NaCl was reduced from 1 to 0.05 MPa for 50% and 91% vol.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, the use of a suitable temporary porogen has been reported many times in previous studies 18 . Shim et al 19 have reported that NaCl can be a good porogen in the PCL matrix due to its good solubility in water and nontoxic effect on living cells. In the other study, Guarino et al 20 showed that the yield stress of PCL scaffolds by the addition of NaCl was reduced from 1 to 0.05 MPa for 50% and 91% vol.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, the use of a suitable temporary space holder has been reported many times in previous studies (Samuel, Kong et al 2022). Shim et al (Shim, Sa et al 2016) have reported that NaCl can be a good space holder in the PCL matrix due to its good solubility in water and nontoxic effect on the living cells. In the other study, Guarino et al (Guarino, Causa et al 2007), showed that the yield stress of PCL scaffolds by addition of NaCl was reduced from 1 to 0.05 MPa for 50 and 91% vol.…”
Section: Introductionmentioning
confidence: 99%